Analysis of payang catch results in Pasie Nan Tigo, Koto Tangah District, Padang City, West Sumatra - Yuspardianto, Yuspardianto; Kamal, Eni; Bukhari, Bukhari; Putra, Cenigo (Acta Aquatica: Aquatic Sciences Journal, 2024)
This research aimed to analyze the results of Payang catches landed in Pasie Nan Tigo, Tangah City District, Padang City. This research used the research object of payang fishing gear in the Pasie Nan Tigo area, Koto Tangah District, Padang City, which was carried out in May 2023. The method used is a descriptive method by making direct observations at the location of the trawl fishing gear in terms of the construction of the fishing gear, fishing area and type of fish caught. Based on the results of this research, the number of payang fishing gear found in Pasie Nan Tigo Village, Koto Tangah District, Padang City is 40 units. The method of operating the payang fishing gear is by circling schools of fish. The results caught by Payang fishing gear are Euthynnus sp, Rastrelliger sp., Katsuwonus pelamis, Stolephorus sp., Trichiurus sp., Leiognathus sp. and so on.Keywords: Rainfall; Turtle; Wave Height; Wind Speed